Implications of corporate innovation investment on environment sustainability with moderating role of managerial stock incentives: A case of the oil and gas sector of the United States of America - Tang, Honglei; Rasool, Zeeshan; Sindhu, Muzammal Ilyas; Naveed, Muhammad; Babar, Samreen Fahim (Frontiers in Environmental Science, 2023)
The purpose of this study is to examine the impact of corporate innovation investment on environmental sustainability in oil and gas companies in the United States of America. We have compiled the empirical data set of 90 major and renowned companies for the time interval 2009 to 2019. To examine the cause and effect relationship between the specific factors, we applied the generalized method of movement and the statistical result reflected that there is a significant and positive relationship between corporate innovation investment and environmental sustainability. This indicates that with the positive inclusion of intangible assets leads to motivation in innovation that enhances the context of environmental sustainability. Managerial stock incentive is significant and positively moderating the relationship of corporate innovation investment and environmental sustainability. Enterprises should not only consider their management stock mechanism during formulation of innovation strategy, but also design the contract according to the innovation level of the enterprise to determine the level of managerial incentive. This study provides insight regarding significant role of corporate innovation which establishes a way forward to environmental sustainability.